Genotypic Diversity of Iranian strains of Ralstonia solanacearum - IZADIYAN, Mahsa; TAGHAVI, S. Mohsen (Phytopathologia Mediterranea, 2011)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 14 false false false <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --><!--[endif] --><!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --><!--[endif] --> During 2007–2009, 170 bacterial isolates were obtained from wilting potato and tomato plants from Iran. Specific polymerase chain reaction (PCR) analyses identified all the isolates as Ralstonia solanacearum. Diversity among the Iranian isolates was determined by a study based on biovar determination, pathogenicity, repetitive sequence PCR and phylotype classification. On the basis of genotypic, phenotypic and pathogenic characteristics two distinct clusters obtained. Cluster I comprised all biovar 2 isolates and cluster II comprised all biovar N2 (2T) isolates. Phylotype-specifi c multiplex PCR (pmx-PCR) indicated that all biovar 2 and N2 belong to phylotype II. This is the first report of phylotype determination of biovars of R. solanacearum with pmx-PCR in Iran.